Driving ability in schizophrenic patients: effects of neuroleptics - Soyka, Michael; Kagerer, Sabine; Brunnauer, Alexander; Laux, Gerd; Möller, Hans-Jürgen (International journal of psychiatry in clinical practice, 2005)
Recent studies indicate that individuals with schizophrenia have a two-fold incidence of traffic accidents. Cognitive and psychomotor impairment as a core feature of schizophrenia and the effects of neuroleptic treatment play an essential role in this respect. Few experimental studies have been conducted so far looking at the effects of neuroleptics on driving ability in schizophrenia. Controlled, randomised trials are totally missing. The limited database indicates that most schizophrenic patients show significant impairment in cognitive functions relevant for driving ability compared to healthy controls. There is some but limited evidence that patients under novel atypical neuroleptics show less impairment compared to conventional neuroleptics. More clinical and experimental studies are warranted.